A Fluorescent Titanium‐based Metal‐Organic Framework Sensor for Nitro‐aromatics Detection. Issue 7 (2nd February 2021) - Zhang, Xin; Yan, Yu; Chen, Faqiang; Bai, Gongxun; Xu, Hui; Xu, Shiqing
Abstract: A rare fluorescent nanoscale titanium‐based metal‐organic framework (MOF) material, Ti6 (μ3 ‐O)6 (μ2 ‐OH)6 (BTB)2 (DMF)2 (ZSTU‐2 ) was synthesized and realized for highly sensitive sensing of nitro‐aromatic compounds. ZSTU‐2 exhibited high fluorescence intensity with blue luminescence and stability in water. ZSTU‐2 exhibited significant luminescent quenching effects upon the addition of nitro‐aromatic compounds, especially for picric acid (PA). The limit of detection (LOD) for PA reaches 2.37 μM and the K sv value is 2.266×10 4 M −1 . Abstract :